2008
DOI: 10.1128/aac.01284-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Phenotypic Susceptibility of Human Immunodeficiency Virus Type 2 Clinical Isolates to Protease Inhibitors

Abstract: We determine phenotypic susceptibility of human immunodeficiency virus type 2 (HIV-2) isolates to amprenavir, atazanavir, darunavir, indinavir, lopinavir, nelfinavir, saquinavir, and tipranavir. Saquinavir, lopinavir, and darunavir are potent against wild-type HIV-2 isolates and should be preferred as first-line options for HIV-2-infected patients. Other protease inhibitors are less active against HIV-2 than against HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 14 publications
6
80
1
2
Order By: Relevance
“…There are currently some phenotypic studies that allow the selection of better first-line therapies than those used a few years ago (16,61), but the knowledge of HIV-2 resistance pathways is still incomplete. Longitudinal data of an individual HIV-2 ϩ patient, in whom the initial ART regimen was associated with the rapid emergence of mutations and virological failure, illustrated that switching to another ART combination was associated with viremia suppression and a decline of cell-associated viral burden (Fig.…”
Section: Relationship Of Plasma and Cell-associated Viral Load With Cmentioning
confidence: 99%
“…There are currently some phenotypic studies that allow the selection of better first-line therapies than those used a few years ago (16,61), but the knowledge of HIV-2 resistance pathways is still incomplete. Longitudinal data of an individual HIV-2 ϩ patient, in whom the initial ART regimen was associated with the rapid emergence of mutations and virological failure, illustrated that switching to another ART combination was associated with viremia suppression and a decline of cell-associated viral burden (Fig.…”
Section: Relationship Of Plasma and Cell-associated Viral Load With Cmentioning
confidence: 99%
“…The inhibitors APV, DRV and SQV were selected due to their distinct effects on the two types of virus. HIV-2 strains were shown to be susceptible to DRV 19 and to SQV, 20,21 while natural resistance to APV was found for several HIV-2 strains. [20][21][22] Thus, crystallographic and kinetic analysis of PR 1M , PR 1 and PR 2 will improve our understanding of the differences in inhibitor potency.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that wild-type HIV-2 is at least partially resistant, in vitro, to the majority of PI FDA approved for the treatment of HIV-1, retaining clinically useful susceptibility only to SQV, LPV, and DRV (13)(14)(15)(16)(17)(18)(19)(20). Although it has long been known that the active centers of HIV-1 and HIV-2 proteases differ by only four amino acids (23), this observation has never been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-2 is at least partially resistant to the majority of the HIV-1 PI approved by the U.S. Food and Drug Administration (FDA); only lopinavir (LPV), darunavir (DRV), and saquinavir (SQV) are active at clinically useful concentrations (13)(14)(15)(16)(17)(18)(19)(20). The determinants of intrinsic PI resistance in HIV-2 are unknown, but previous studies have identified just four residues in the protease binding cleft, at amino acid positions 32, 47, 76, and 82, that differ between HIV-1 and HIV-2 (6,(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%